Strong structuration theory in accounting research - Kholeif, Ahmed (2021)
The purpose of this paper is to discuss the interdisciplinary use of strong structuration theory and consider the impact of this for accounting research. The paper also provides an overview of the contributions advanced by the other papers in this special issue of Accounting, Auditing and Accountability Journal (AAAJ). Design/methodology/approach This paper draws together and identifies key issues and themes related to the rapidly evolving interdisciplinary use of strong structuration theory and considers the relevance of these issues to accounting research. Findings The paper highlights that there is a growing use of strong structuration theory in a number of disciplines, such as in healthcare, learning studies, management, migration studies and childcare as well as in accounting. Within the accounting discipline, whilst the interest began in management accounting and control, there are ongoing studies of the not-for-profit sector, social and environmental accounting, financial reporting standards and audit. Using strong structuration theory, researchers are more interested in the people (individually or collectively) and their analysis of their conduct and context. They are moving forwards from an overly static use of the quadripartite framework to a more dynamic approach that also includes the other important central elements of strong structuration that focus on the issue of agency in situ rather than on structure cut off from agency. Research limitations/implications The paper provides important insights into emerging issues and developments in strong structuration theory that have clear relevance to accounting research and practice as well as other disciplines. Originality/value This paper, and other contributions to this special issue of AAAJ, provide a basis and a research agenda for accounting scholars seeking to undertake empirical research using Stones’ strong structuration theory.